2019
DOI: 10.3390/polym11081295
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Carrier Type for Enhanced Thermoelectric Performance of Single-Walled Carbon Nanotubes/Polyethyleneimine Composites

Abstract: Thermoelectric (TE) generators consisting of flexible and lightweight p- and n-type single-walled carbon nanotube (SWCNT)-based composites have potential applications in powering wearable electronics using the temperature difference between the human body and the environment. Tuning the TE properties of SWCNTs, particularly p- versus n-type control, is currently of significant interest. Herein, the TE properties of SWCNT-based flexible films consisting of SWCNTs doped with polyethyleneimine (PEI) were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…More recently, rapid research progress has been made in exploring flexible anode materials delivering high storage capacity and remarkable long-term cyclability [15][16][17]. As an allotrope of carbon, CNT electrodes offer several outstanding properties, such as excellent flexibility, fast charge transport, large surface-to-volume ratio, good chemical stability, high electrical conductivity and high reversible capacity [18][19][20][21][22][23][24][25][26]. Several methods to synthesize CNT have been demonstrated, e.g., chemical vapor deposition (CVD) [25,27], pyrolysis [28], arc 2 of 16 discharge [29,30], laser ablation [31] and electrolysis [32].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, rapid research progress has been made in exploring flexible anode materials delivering high storage capacity and remarkable long-term cyclability [15][16][17]. As an allotrope of carbon, CNT electrodes offer several outstanding properties, such as excellent flexibility, fast charge transport, large surface-to-volume ratio, good chemical stability, high electrical conductivity and high reversible capacity [18][19][20][21][22][23][24][25][26]. Several methods to synthesize CNT have been demonstrated, e.g., chemical vapor deposition (CVD) [25,27], pyrolysis [28], arc 2 of 16 discharge [29,30], laser ablation [31] and electrolysis [32].…”
Section: Introductionmentioning
confidence: 99%
“…CPs/inorganic thermoelectric composites are one of the major types of organic thermoelectric materials which combine the large Seebeck coefficient feature of CPs with the low thermal conductivity and high electrical conductivities of inorganic nanomaterials [26][27][28][29][30][31][32][33]. Single wall carbon nanotubes (SWCNTs) are one type of attractive carbon nanomaterial for forming thermoelectric composites, attributed to their high electric conductivity and excellent flexibility [27].…”
Section: Introductionmentioning
confidence: 99%
“…Single wall carbon nanotubes (SWCNTs) are one type of attractive carbon nanomaterial for forming thermoelectric composites, attributed to their high electric conductivity and excellent flexibility [27]. Therefore, various kinds of CPs/SWCNTs composites have been prepared and their thermoelectric properties were investigated [26][27][28][29][30][31][32][33]. It was found that the interfacial interactions between SWCNTs and CPs are crucial to enhance the charge carrier mobility for the composites.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, the thermoelectric performance of SWCNT flexible films doped with polyethyleneimine (PEI) and Nafion were assessed. The nanocomposites were manufactured via simple solution casting followed by vacuum filtration [33]. The SWCNT/PEI nanocomposites were switched from p-to n-type upon addition of PEI contents higher than 13 wt %.…”
mentioning
confidence: 99%